UIN Ar-Raniry Student's Perception of Online Learning Process During The Covid-19 Pandemic - Eva Nauli Taib; Widya Sari; Nafisah Hanim; Mauli Ismaini (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2022)
The Covid-19 pandemic has begun to attack Indonesia and has penetrated the world of education. The policy taken by the government to save the world of education is to conduct online learning. Online learning is the main solution in the learning process. However, in the process of implementation, online learning has obstacles that must be faced by students and students. This study aims to describe UIN Ar-Raniry student’s perceptions of online learning during the Covid-19 pandemic. The method used in this study is a quantitative and qualitative approach with an exploratory descriptive method. A quantitative approach is used to tabulate the percentage of students' perceptions of the online learning process during the Covid-19 pandemic, while a qualitative approach is used to describe UIN Ar- Raniry student’s perceptions of the online learning during the Covid-19 pandemic. The results of this study indicate that UIN Ar- Raniry students' perceptions of online learning are 70.24% which can be categorized in the good category. It shows that the online learning process carried out during this pandemic has been going well, although there are still some obstacles that students must face in implementing online learning. Constraints faced by students in the form of unstable networks, data packets, and a less conducive learning environment.